A Digital Platform Designed for Youth Mental Health Services to Deliver Personalized and Measurement-Based Care - Iorfino, Frank; Cross, Shane P.; Davenport, Tracey; Carpenter, Joanne S.; Scott, Elizabeth; Shiran, Sagit; Hickie, Ian B. (Frontiers in Psychiatry, 2019)
Those mental disorders that commonly emerge during adolescence and young adulthood are associated with substantial immediate burden and risks, as well as potentially imparting lifetime morbidity and premature mortality. While the development of health services that are youth-focused and prioritize early intervention has been a critical step forward, an ongoing challenge is the heterogeneous nature of symptom profiles and illness trajectories. Consequently, it is often difficult to provide quality mental health care, at scale, that addresses the broad range of health, social and functional needs of young people. Here, we describe a new digital platform designed to deliver personalized and measurement-based care. It provides health services and clinicians with the tools to directly address the multidimensional needs of young people. The term ‘personalized’ describes the notion that the assessment of, and the sequence of interventions for, mental disorders are tailored to the young person - and their changing needs over time. While, ‘measurement-based’ describes the use of systematic and continuing assessment of a young person’s outcomes over the entire course of clinical care. Together, these concepts support a framework for care that transcends a narrow focus on symptom reduction or risk reduction. Instead it prioritizes a broader focus on enhancing social, health and physical outcomes for young people, and a commitment to tracking these outcomes throughout this key developmental period. Now, with twenty-first century technologies, it is possible to provide health services with the tools needed to deliver quality mental health care.